Methods in Year 50: Preserving the Past and Preparing for the Future - Haux, R.; Aronsky, D.; Leong, T. Y.; McCray, A. T. (Methods of Information in Medicine, 2011)
Background: Founded in 1962 and, therefore, the oldest international journal in medical informatics, Methods of Information in Medicine will publish its 50th volume in 2011. At the start of the journal’s sixth decade, a discussion on the journal’s profile seems appropriate.Objectives: To report on the new opportunities for online access to Methods publications as well as on the recent strategic decisions regarding the journal‘s aims and editorial policies.Methods: Describing and analyzing the journal’s aims and scope. Reflecting on recent publications and on the journal’s development during the last decade.Results: From 2011 forward all articles of Methods from 1962 until the present can be accessed online. Methods of Information in Medicine stresses the basic methodology and scientific fundamentals of processing data, information and knowledge in medicine and health care. Although the journal‘s major focus is on publications in medical informatics, it has never been restricted to publications only in this discipline. For example, articles in medical biometry, in or close to biomedical engineering, and, later, articles in bioinformatics continue to be a part of this journal.Conclusions: There is a continuous and, as it seems, ever growing overlap in the research methodology and application areas of the mentioned disciplines. As there is a continuing and even growing need for such a publication forum, Methods of Information in Medicine will keep its broad scope. As an organizational consequence, the journal’s number of associate editors has increased accordingly.
Keywords: Medical informatics; health informatics; biomedical informatics; bioinformatics; biomedical engineering; medical biometry; publishing